Parenting Style, Self-Esteem and Student Performance in the United Arab Emirates - Negmeldin Omer Alsheikh; Gowri Parameswaran; Hala Ethoweris (Arizona State University, 2010)
The impact of parenting styles on 4-7th grade studentsâ performance and self-esteem was analyzed within a sample of United Arab Emirates (UAE) public school children. A sample of 162 children (50% boys, 50% girls) reported on their parentsâ child-rearing practices. Parenting styles were classified into one of three groups (autonomy granting, demandingness, or responsiveness). The results show that demandingness was found to have a significant impact on GPA scores. Both gender and age were significantly related to parenting styles. Factor analysis results suggested that Family Cohesion and Effort were positively related to school performance and Self-autonomy was negatively related to school performance. Self-esteem was not significantly related to any of the variables studied.